Pengaruh Keterikatan Emosional terhadap Kepuasan Pelanggan Pada Pasien Rehabilitasi Medik RSUD Subang - Gugyh Susandy; Nadya Nur Fadhilla; Tia Mulyana (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
This study aims to determine whether emotional attachment influences customer satisfaction among medical rehabilitation patients at Subang Regional Public Hospital. The study sample consisted of 61 respondents who were medical rehabilitation patients at Subang Regional Public Hospital. The independent variable was emotional attachment, and customer satisfaction served as the dependent variable. This quantitative study utilized data collected via a questionnaire. Data analysis in this study involved descriptive statistics, data quality checks, classical assumption tests, single linear regression analysis, and hypothesis testing using SPSS. The results indicate that, the variable of emotional attachment influences customer satisfaction among medical rehabilitation patients at Subang Regional Public Hospital. This influence is positive and significant, meaning that higher emotional attachment leads to increased customer satisfaction. Furthermore, the coefficient of determination test shows an R Square value of 0.470, indicating that emotional attachment explains 47% of the variance in customer satisfaction, while the remaining 53% is explained by other factors outside this model.